Analisis Pengaruh Dimensi Fraud Diamond Terhadap Perilaku Kecurangan Mahasiswa Akuntansi - Feri Siswanto; NPMA Durya (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
Disclosure of fraud committed by accounting students uses the Diamond Fraud concept. This study aims to determine the effect of the Fraud Diamond aspect on academic fraud in student circles. In this study, the research samples were 104 students who were taking auditing courses at Semarang State University in the accounting study program batches of 2020 and 2021. The Multiple Regression Analysis used in this study was to examine the combined and individual effects of independent variables on variables dependent. This analysis is preceded by a classical assumption test, which includes a normality test, multicollinearity test, autocorrelation test, and heteroscedasticity test. While the F test and t test are used for hypothesis testing. The results of this study indicate that pressure has no effect on fraud, rationalization has no effect on fraud and opportunity has no effect on fraud, while ability has an effect on fraud. The advice we can take regarding this discussion is the importance of prioritizing ethical principles and social values ​​in the academic environment, especially the Semarang State University campus environment.